2006
DOI: 10.1136/bjo.2006.099069
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional assessment of the macular region in patients with glaucoma

Abstract: Purpose: To investigate the correlation of a structural measure of the macular area (optical coherence tomography (OCT)) with two functional measures (10-2 Humphrey visual field (HVF) and multifocal visual evoked potential (mfVEP)) of macular function. Methods: 55 eyes with open-angle glaucoma were enrolled. The 10-2 HVF was defined as abnormal if clusters of >3 points with p,5%, one of which had p,1%, were present. The mfVEP was abnormal if probability plots had >2 adjacent points with p,1%, or >3 adjacent po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 26 publications
3
40
0
5
Order By: Relevance
“…This result was in agreement with Orzalesi's report that documented the presence of decreased retinal sensitivity corresponding to a localized RNFLD using a high density of targets in scanning laser ophthalmoscopy [7]. Kanadani et al [26] evaluated the macular area in glaucoma patients with an HFA 10-2 threshold test and reported that 98.2 % of eyes with glaucoma had perimetric changes. The 24-2 distribution of test locations in the central 10°was limited to 12 locations, each separated by 6°.…”
Section: Discussionsupporting
confidence: 89%
“…This result was in agreement with Orzalesi's report that documented the presence of decreased retinal sensitivity corresponding to a localized RNFLD using a high density of targets in scanning laser ophthalmoscopy [7]. Kanadani et al [26] evaluated the macular area in glaucoma patients with an HFA 10-2 threshold test and reported that 98.2 % of eyes with glaucoma had perimetric changes. The 24-2 distribution of test locations in the central 10°was limited to 12 locations, each separated by 6°.…”
Section: Discussionsupporting
confidence: 89%
“…This may reflect a more focal glaucomatous damage in the patients that may be lost if larger areas are averaged together. Our finding of a significant central loss in the RMS amplitudes of the DC, IC-1, and IC-2 of the 2-global flash mfERG is in agreement with previous reports of macular involvement in glaucoma [20][21][22]. It is also consistent with previous OCT findings of macular involvement in glaucoma, where a qualitative reduction in the thickness of the RGC layer by computeraided manual segmentation procedure corresponds to local losses in visual field sensitivity [23].…”
Section: Discussionsupporting
confidence: 82%
“…Diversos autores demonstraram que a perda de alguns setores da espessura macular tiveram uma correlação tão boa com o defeito de campo visual quanto à perda da CFNR em pacientes com atrofia em banda do nervo óptico (7) . Outros autores demonstraram que em pacientes portadores de glaucoma em estágios mais avançados, a redução na espessura macular foi mais significativa na região macular inferior e apresentou melhor correlação com os defeitos funcionais do que aquela obtida com a CFNR peripapilar (10) . A avaliação da espessura macular pode também ser importante quando se pretende quantificar a perda neural em afecções do nervo óptico que cursam com edema do disco óptico.…”
Section: Discussàounclassified